Analysis of the importance of five new spectral indices from WorldView-2 in tree species classification. Issue 3 (1st September 2020) - Liu, Huaipeng; An, Huijun
ABSTRACT: Spectral information mining plays a signiﬁcant role in tree species classiﬁcation using remote sensing images but a measure of the importance of the mined features is also necessary. We created five new spectral indices and used MLC-RFI to determine their importance. The results showed that these spectral indices had a positive eﬀect on tree species classiﬁcation, and their importance was ranked as follows: PAI578 > PAI678 > TAI578 > TAI678 > SI57 . The experimental results showed that important spectral indices for tree species classiﬁcation can be created and that it is beneﬁcial to mine spectral information from remote sensing images.